1985
DOI: 10.1063/1.448846
|View full text |Cite
|
Sign up to set email alerts
|

O+2 ions dissociation studied by threshold photoelectron–photoion coincidence method

Abstract: The threshold photoelectron–photoion coincidence method was used to study O+2 dissociation. Previous results were confirmed and a careful analysis of the time of flight peak shapes using a Monte Carlo simulation gave us new results. The lifetime of the B 2Σ−g state was measured to be 70∓25 ns independently of the vibrational quantum number. The III 2∏u state which dissociates towards the O+(2D0)+O(3P) and O+(2P0)+O(3P) limits shows anisotropic distribution of fragment ions. The c 4Σ−u(v=0) state which was prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 21 publications
6
50
0
Order By: Relevance
“…In coincidence studies, the same conclusion was found based on the photoelectron-photoion coincidence ͑PEPICO͒ spectroscopy 11 and threshold-PEPICO ͑TPEPICO͒ study. 39 However, most of the studies measured the ␤ m close to the threshold, and modulations due to Rydberg autoionization series to the inner-valence ionization states are very likely to occur in this energy region. Actually, in the PEPICO study, Eland et al 11 described the measured ␤ m near the threshold, which, ranged from 0 to Ϫ1, and had some subtle structures.…”
Section: B Cross Sections and Asymmetry Parameters For The Photoionimentioning
confidence: 99%
“…In coincidence studies, the same conclusion was found based on the photoelectron-photoion coincidence ͑PEPICO͒ spectroscopy 11 and threshold-PEPICO ͑TPEPICO͒ study. 39 However, most of the studies measured the ␤ m close to the threshold, and modulations due to Rydberg autoionization series to the inner-valence ionization states are very likely to occur in this energy region. Actually, in the PEPICO study, Eland et al 11 described the measured ␤ m near the threshold, which, ranged from 0 to Ϫ1, and had some subtle structures.…”
Section: B Cross Sections and Asymmetry Parameters For The Photoionimentioning
confidence: 99%
“…A true coin-cidence signal is then the signature of a double-ionization event and will be recorded each time the scanned photon energy goes through the threshold of a double-ion state. A TPESCO spectrum obtained in this way is then the double-ionization analog of threshold photoelectron spectra used in the study of single-ionization processes [21][22][23].…”
mentioning
confidence: 99%
“…10 23.75 eV, respectively. 83 These measurements indicate that the majority of O++O fragments from O2 (c4Eu, v+ = 0), and 1) are produced in the first and second dissociation limits with substantial kinetic energy releases.71, 85 An upper bound of 200 ns was reported by Guyon et a1. 84 for the rd's of Oa (c4Eu , v+ = 0) based on simulation of the TOF TPEPICO spectrum for O+.…”
Section: O2(c4eu V+ = 01)mentioning
confidence: 86%
“…83 The OZ (d4Eg , f4II9) potential curves are predicted to cross that for Oa (B2E9) near its equilibrium distance between v+ = 0 and 1. 78,86 According to previous theoretical calculations, the Oa ( 12Eg) state whose potential energy curve is parallel to that of values for v+ = 0-7 is likely the result of specific intersections between the potential energy surfaces of these dissociative states and that of 02 (B2E9 ).…”
Section: 333)93mentioning
confidence: 98%
See 1 more Smart Citation